2005
DOI: 10.1111/j.1432-2277.2004.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential value of high-dose mizoribine as rescue therapy for ongoing acute humoral rejection

Abstract: Summary Mizoribine (MZ) inhibits the proliferation of lymphocytes selectively via inhibition of inosine monophosphate dehydrogenase, like mycophenolate mofetil (MMF). The clinical dosage of MZ (2–5 mg/kg) is much lower than that of MMF (20–60 mg/kg). The purpose of this study was to examine whether high‐dose MZ would be effective for treatment of acute humoral rejection. Renal transplantation was performed in a different pig strain combination. Group 1 (n = 2) received no treatment. Group 2 (n = 4) received cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…This is supported by our and others (36,37) data in vivo and in vitro which were showed the MZ had lower potential to inhibit cell proliferation assays and rejection in mouse heart transplantation than MMF. In addition, it has been reported that high-dose MZ therapy was effective experimentally for ongoing acute humoral rejection (38) and clinically for frequently relapsing steroid-dependent nephritic syndrome (39). Following these results, a clinical trial of highdose of MZ therapy for renal transplantation is being conducted in several Japanese hospitals.…”
Section: Discussionmentioning
confidence: 96%
“…This is supported by our and others (36,37) data in vivo and in vitro which were showed the MZ had lower potential to inhibit cell proliferation assays and rejection in mouse heart transplantation than MMF. In addition, it has been reported that high-dose MZ therapy was effective experimentally for ongoing acute humoral rejection (38) and clinically for frequently relapsing steroid-dependent nephritic syndrome (39). Following these results, a clinical trial of highdose of MZ therapy for renal transplantation is being conducted in several Japanese hospitals.…”
Section: Discussionmentioning
confidence: 96%
“…2) Mizoribine is a highly hydrophilic and weakly acidic compound, 3) and is not metabolized in the body. Mizoribine binds poorly to plasma proteins (2.3%), 4) and is excreted predominantly in the urine (81.8% at 6 h after oral administration of 100 mg mizoribine in healthy subjects) 5) ; therefore, renal function has been considered to be one of the main causes of the pharmacokinetic variability of mizoribine. On the other hand, Ihara et al evaluated the pharmacokinetics of mizoribine in 14 kidney transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…There is a positive relationship between the serum level of mizoribine and its clinical efficacy without causing severe adverse effects [22,23,24]. This indicates that pulse therapy or high-dose of mizoribine is applicable in clinical use.…”
Section: Introduction For Mizoribinementioning
confidence: 99%